Anisotropic magnetic polymer nanocomposite with self-assembled chains of titania-coated magnetite nanoparticles. (June 2016) - Allia, P.; Barrera, G.; Nardi, T.; Leterrier, Y.; Tiberto, P.
Graphical abstract: Abstract: An anisotropic magnetic nanocomposite has been prepared by incorporating magnetite nanoparticles (average size: 19 nm) in titania (TiO2 ) particles with a typical size of about 100 nm, which are subsequently dispersed in a liquid epoxy monomer cured under an inhomogeneous magnetic field. The magnetic force triggers the formation of elongated, self-assembled chains made of aggregated titania particles containing the magnetic cores. The chains have an average length of 7 × 10 -5 m and are almost homogeneously distributed throughout the sample; their length and degree of directional order decrease with distance from the magnet producing the magnetic field. FC/ZFC curves and isothermal hysteresis loops of the anisotropic nanocomposite have been studied under a magnetic field applied either parallel or perpendicular to the chains. The anisotropy of the magnetic response is explained by modeling the chains as individual magnetic entities at the mesoscopic level owing to the magnetic dipolar interaction among the embedded magnetite nanoparticles.